Expression of ribosomal and actin network proteins and immunochemotherapy resistance in diffuse large B cell lymphoma patients. (16th May 2018) - Bram Ednersson, Susanne; Stenson, Martin; Stern, Mimmie; Enblad, Gunilla; Fagman, Henrik; Nilsson‐Ehle, Herman; Hasselblom, Sverker; Andersson, Per‐Ola
Summary: Diffuse large B cell lymphoma (DLBCL) patients with early relapse or refractory disease have a very poor outcome. Immunochemotherapy resistance will probably, also in the era of targeted drugs, remain the major cause of treatment failure. We used proteomic mass spectrometry to analyse the global protein expression of micro‐dissected formalin‐fixed paraffin‐embedded tumour tissues from 97 DLBCL patients: 44 with primary refractory disease or relapse within 1 year from diagnosis (REF/REL), and 53 who were progression‐free more than 5 years after diagnosis (CURED). We identified 2127 proteins: 442 were found in all patients and 102 were differentially expressed. Sixty‐five proteins were overexpressed in REF/REL patients, of which 46 were ribosomal proteins (RPs) compared with 2 of the 37 overexpressed proteins in CURED patients ( P  = 7·6 × 10 −10 ). Twenty of 37 overexpressed proteins in CURED patients were associated with actin regulation, compared with 1 of 65 in REF/REL patients ( P  = 1·4 × 10 −9 ). Immunohistochemical staining showed higher expression of RPS5 and RPL17 in REF/REL patients while MARCKS‐like protein, belonging to the actin network, was more highly expressed in CURED patients. Even though functional studies aimed at individual proteins and protein interactions to evaluate potential clinical effect are needed, our findings suggest new mechanisms behind immunochemotherapy resistance in DLBCL.